PWE-100 How Commonly Does Faecal Calprotectin Alter Management in Patients with I.B.D?. (4th June 2013) - Allison, M; Hu, M; Puritz, S; Richards, T; El-Farhan, N
Abstract : Introduction: Faecal calprotectin is often measured in patients with inflammatory bowel disease (IBD). Some believe it is a useful surrogate marker for mucosal healing, and normal values may strengthen the case for stopping biological agents. It is unclear, however, to what extent such measurements alter patient investigation and management over standard history taking, examination and routine blood tests. Methods: We reviewed all faecal calprotectin results from samples submitted by 98 adults with IBD between February 2010 and April 2012. Using the Health Board's Clinical Workstation relevant outpatient letters, results of subsequent investigations and changes of treatment were reviewed. A calprotectin value of >60 ug/g was considered elevated. Results: Seventy of the patients (71%) had an elevated result. Their outcomes are summarised in the table. Most changes in patient management and investigation requests were made at the same visit as the calprotectin request. Elevated results prompted escalation of treatment in 6 patients. Among 28 patients with a normal result, symptoms prompted escalation of treatment (6 patients) and colonoscopy (3 patients) before knowledge of the result, No endoscopic or radiological investigations or changes of treatment occurred in 12 patients. In no cases was maintence treatment reduced on the basis of a normal result. Measurements seemed to help managment in 7 patients: there were 2 with previous equivocal investigations who may have avoided further tests, and there were 5 whose symptoms were in excess of objective findings who could be reassured about absence of active inflammation). Conclusion: This study casts doubt on the value of faecal calprotectin measurement in the follow-up of most patients with IBD. Normal results assisted in the reassurance of some patients whose symptoms seemed out of proportion to objective evidence of disease activity. There were no instances of a normal result leading to scaling back of maintenance treatment, and none stopped biological agents. Disclosure of Interest: None Declared.